Associação entre microalternância de onda T e arritmias ventriculares na doença de chagas - Bárbara Carolina Silva Almeida (2017)
Sudden death is the most frequent death mechanism in Chagas disease, responsible for 55 to 65% of the death in patients with Chagas cardiomyopathy. The most often involved electrophysiological mechanisms are ventricular tachycardia and ventricular fibrillation. The implantable cardioverter defibrillator (ICD) has a beneficial role in preventing sudden death due to malignant ventricular arrhythmias in cardiomyopathies of several etiologies. The ICD implant in secondary prevention of sudden death is well established in Chagas cardiomyopathy, but the implant in primary prevention is not. A correct patient selection and proper identification of patients at risk of sudden death is important to allow an adequate use of this therapy. The microvolt T wave alternans (MTWA) is a non-invasive test that measures fluctuations in T wave amplitude and morphology. The non-negative test (positive or indeterminate) associates with ventricular arrhythmias in different clinical conditions, with a high negative predictive value for identifying patients at risk. The role of MTWA in patients with Chagas cardiomyopathy is uncertain, although it seems to be promising. Objective: To evaluate the presence of association between MTWA and ventricular arrhythmias in patients with Chagas cardiomyopathy. Method: This is an observational, case-control study. The recruitment occurred in a tertiary hospital in Brazil. Patients with Chagas cardiomyopathy and history of ventricular arrhythmias were the group of cases and patients with Chagas cardiomyopathy and no history of ventricular arrhythmias were the control group. We performed MTWA tests in all patients and the result classified as negative and non-negative. Results: We recruited 96 patients, 45 cases (46.8%) and 51 controls (53.1%). The groups were heterogeneous, presenting difference in gender, age and left ventricular ejection fraction. The tests were non-negative in 51 patients (53.1%), of those 36/45 (80%) belonged to the case group and 15/51 (29.4%) to the control group, OR=9.60 (CI95%: 3.41 – 27.93). The non-negative result, after adjusted for known confounding factors in a logistic regression model, continued to be associated with malignant ventricular arrhythmias, with OR=5.17 (CI95% 1.05 – 25.51). Conclusion: Patients with Chagas cardiomyopathy and a history of malignant arrhythmias presents a higher frequency of non–negative MTWA when compared with patients with no history of previous arrhythmia.